(untitled) (Research, Society and Development, 2020)
Objective: To raise reflection and understand the difficulties faced by transgender and transgender people, a marginalized and stigmatized population that has suffered since childhood with symbolic and physical violence resulting in a social and psychological vulnerability in the Unified Health System (SUS). Methodology: It is a narrative review of the literature, which aims at the interpretation, reflection and analysis of the subject, of a qualitative nature. An online search was carried out in the SCIELO, PUBMED AND LILACS databases, which were restricted in the year 2009 to 2020, finding 16 articles after inclusion and exclusion critério. Bibliographic review: After researching the articles, it was noticed that most of the articles that correlated transsexuality and medical care speak of pathologies related to social characterization and the stigma of prostitution and sexually transmitted infections that this sexual and gender minority carries. In addition, it was observed difficulty in the treatment in an adequate way to make the patient comfortable, and, with that, build for a good doctor-patient relationship, which influences so that there are gaps in the attendance and consequently a deficient anamnesis, as one must take into account the psychological, social and environmental framework for a good consultation. Final considerations: Combating prejudice so that there is an improvement in the doctor-patient relationship and a more skilled system for receiving transsexuals avoiding the evasion of this population, which needs medical attention and monitoring, is urgent.